2004
DOI: 10.1002/ffj.1289
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the essential oil of nine Eucalyptus species growing in Morocco

Abstract: The essential oils obtained by steam distillation from the leaves of nine Eucalyptus species (E. cinerea F. Muell., E. baueriana F. Muell., E. smithii R. T. Baker, E. bridgesiana R. T. Baker, E. microtheca F. Muell., E. foecunda Schau., E. pulverulenta Sims, E. propinqua Deane and Maiden, E. erythrocorys F. Muell.) of Moroccan origin have been analysed using GC and GC–MS. A total of 83 constituents were identified. All the species investigated were found to possess an oil rich in 1,8‐cineole (>68%). In five spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 7 publications
2
40
0
5
Order By: Relevance
“…31) Moreover, the chemical composition of the E. bridgesiana essential oil consists of 82.6% 1,8-cineole. 10) The variations in the percentages of essential oil component might be due to extraction of essential oil from different plant resources and by different extraction procedures. In the composition of the C. martinii essential oil, geraniol (52.49%) and geranyl acetate (12.01%) were the major compounds (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31) Moreover, the chemical composition of the E. bridgesiana essential oil consists of 82.6% 1,8-cineole. 10) The variations in the percentages of essential oil component might be due to extraction of essential oil from different plant resources and by different extraction procedures. In the composition of the C. martinii essential oil, geraniol (52.49%) and geranyl acetate (12.01%) were the major compounds (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Several species are widespread throughout the world, including Eucalyptus bridgesiana. 10) Eucalyptus essential oils are found in the leaves, fruits, buds, and bark of the tree, 11,12) but only a small number of studies have described the essential oil of E. bridgesiana. Cymbopogon martinii produces a geraniol-rich, commercially valuable essential oil.…”
mentioning
confidence: 99%
“…Further, yields of different Eucalyptus EO from fresh plant materials of some selected Congolese trees varied significantly from one species to another. Disparity with these yields compared to those formerly reported in the literature for the Eucalyptus aromatic plants collected in other geographic areas in the world could be linked to several factors such as climate, nature of the sol, time of collection, mode of extraction and the age of the tree [11,17].…”
Section: Yield Of Eucalyptus Essential Oilmentioning
confidence: 99%
“…Similarly LI & Madden (1995) found that the essential oils obtained from leaves of E. regnans, E. deligatensis, E. nitens, E. denticulata and E. gobulus grown in eight arboreta varied significantly within species and within provenances. It was also demonstrated that E. cinerea from Morocco (Zrira et al, 2004) was poor in essential oils (0.26%) than those cultivated in India (2.55 to 2.87%) (Kiran Babu & Singh, 2009). …”
Section: Oil Yieldsmentioning
confidence: 99%
“…These methods affect the final yield of the oil and it varied from 0.1± 0.1 to 5.7±0.5 7% (Elaissi et al, 2010a;Elaissi et al, 2010b). High levels of 1,8-cineole (87.8%) were found for the majority of the Eucalyptus species (Zrira et al, 2004;Elaissi et al, 2010c). Generally, the yields and composition of the oils varies and it depending on species, used part, plant origin zone, collection period, growth stage of the plant as well extraction methods and storage conditions (Arango-Bedoya et al, 2012).…”
Section: Introductionmentioning
confidence: 99%